Pembatalan Atas Sengketa Sertifikat Hak Milik Atas Tanah (Studi Putusan Pengadilan Negeri Sukoharjo No.55/Pdt.G/2014/PN.SKH) - Jati, Dewi Nawang, Shalman Al Farizi, S.H., M.Kn (2017)
This study aims to determine the factors causing land ownership certificate canceled by the court Sukoharjo District Court No.55 / Pdt.G / 2014 / PN.SKH and to determine the legal protection for holders of land title certificates of good will. The research method using an empirical approach yuridids with primary data in the form of interviews and secondary data from the materials library. Data were collected by literature study and field study with qualitative data analysis. The results of this study indicate that (1) the factors causing the certificate of title for the land is canceled court based on the decision of the District Court Sukoharjo for their actions against the law and the role of PPAT and Land Office of the less scrupulous in the correctness of the data (2) The legal protection for holders of certificates of land rights good will not be given to a defendant who unlawfully in the hang.